Estudo retrospectivo da reabilitação do edentulismo com um novo protocolo de prótese fixa implantossuportada - Carneiro-Campos, Luis Eduardo (2019)
Edentulism is a public health problem, with direct impact over quality of life. Considering this fact, this Doctoral Thesis will pursue four specific objectives: 1 – Evaluate the influence of different maxillary dentitions on the survival rate of mandibular metal-resin implant-fixed complete denture, by means of systematic reviews and meta-analysis; 2 – Present a new multifunctional template design for immediate loading procedures, by means of a case report and 3 – Analyze rehabilitation protocol survival of mandibular metal-resin implant-fixed complete denture, supported by 3 implants, opposed by conventional dentures. In a total of 112 natural, 69 implant-supported and 204 removable dentitions, the general prevalence of failure was respectively 5.4% (6/112; IC 95% [2.3 a 10.76]), 13,99% (20/69; IC 95% [0.77 a 39.41]) e 4.9% (10/204; IC 95% [0.69 a 12.18]). There were no statistical differences between natural and removable dentitions (difference = 0,00 [-0.06, 0.06]; P = 0.93; I2 = 27%), or not even between natural and implant-supported (difference risk = 0,00 [-0.06, 0.07]; P = 0.97; I2 = 0%). With moderate certainty of evidence it is suggested that natural maxillary dentitions do not affect the survival rate of mandibular mandibular metal-resin implant-fixed complete denture differently from other prosthetic designs. The multifunctional template precisely transferred the surgical implants locations, the impression, the vertical dimension and data transfer to the dental technician. Radiographic cantilever extensions varied from 1.7 mm a 22.9 mm. Intra-Class Correlation (ICC) presented values over 0.9. T-test returned values of p>0.05 for all groups. From fifty mandibular prostheses, installed over 150 implants, 10 implants failed. Technical complications observed were abutment screw loosenings (3,0%), prosthetic screw loosenings (17%), prosthetic screw fractures (1%), superstructure detachments (16%), framework fracture (2%), fractures of maxillary dentures (6%) and loss of mandibular prosthesis (4%). Cumulative survival rates of implants and mandibular prosthesis were respectively 93.3% and 96%. Main peri-implant complications were biofilm formation, bleeding on probing and pain, which were controlled during maintenance visits. None of the evaluated variables influenced clinical failures and/or technical complications in statistical significant level. The guided surgery for the installation of mandibular implants on the mandibular symphysis can be performed with enough predictability, using low cost multifunctional templates. The use of maxillary dentures as opposed mandibular metal-resin implant-fixed complete dentures, supported by three implants, being one in the vertically placed, in the mandibular symphysis, and the other two distally tilted in parasymphisary regions, is a reliable, and should be be encouraged for the treatment of edentulism in global scale.